2012
DOI: 10.1167/iovs.12-10182
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Properties of Regulatory T Cells Generated by Incubation of Peripheral Blood Mononuclear Cells with Supernatants of Human RPE Cells

Abstract: PURPOSE.To determine whether supernatants of human retinal pigment epithelium (RPE) cells can convert CD4 þ T cells into regulatory T cells (Tregs) under Treg-induction conditions in vitro and in vivo.METHODS. Peripheral blood mononuclear cells were cocultured with supernatants from TGFb2-pretreated human RPE lines on anti-CD3-coated plates. Cells were then separated with a CD4 þ CD25 þ Treg isolation kit and cultured with supernatants from RPE, anti-CD3/CD28 antibodies, high-dose IL-2, and TGFb2. By flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 34 publications
(61 reference statements)
3
20
0
1
Order By: Relevance
“…either defined through CFSE lo or CD40L/CD69+ in response to specific antigen stimulation). Furthermore, our data show that the iTreg population was CD45RO+ (and CD45RA neg ), Helios lo/neg , CD49b+/LAG3+, Foxp3+, and IL-10+; therefore, the iTreg we identified with these markers are consistent with other studies 3236 and are possibly Foxp3+ Tr1 cells 28,34,38,39 . Moreover, we demonstrated that the iTreg population induced through peanut OIT was specific in suppression of autologous Teff proliferation in response to peanut, not other antigens.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…either defined through CFSE lo or CD40L/CD69+ in response to specific antigen stimulation). Furthermore, our data show that the iTreg population was CD45RO+ (and CD45RA neg ), Helios lo/neg , CD49b+/LAG3+, Foxp3+, and IL-10+; therefore, the iTreg we identified with these markers are consistent with other studies 3236 and are possibly Foxp3+ Tr1 cells 28,34,38,39 . Moreover, we demonstrated that the iTreg population induced through peanut OIT was specific in suppression of autologous Teff proliferation in response to peanut, not other antigens.…”
Section: Discussionsupporting
confidence: 91%
“…The method of identification of iTreg was consistent with other publications 3236,49,68 in which iTreg were defined as proliferating CD4+CD25 hi Foxp3+ cells (i.e. either defined through CFSE lo or CD40L/CD69+ in response to specific antigen stimulation).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since there are many reports showing almost the same activity of ARPE-19 cell monolayers to cultured primary RPE [8][9][10][11], the conditioned media of cultured ARPE-19 cells were assayed to see whether they suppress phagolysosome activation in phagocytizing macrophages. The ARPE-19 cells were cultured to confluence, or kept subconfluent before changing the media to the serum-free media for an additional 24 hours of incubation.…”
Section: The Effects Of Cultured Arpe-19 Cells On Macrophage Phagolysmentioning
confidence: 99%
“…These cells grow to a confluent monolayer, and have been used to study the effects of oxidants and cytokines involved in RPE changes related to age-related macular degeneration [8,9]. These cell lines when treated with TGF-β2 have been found to mediate the activation of Treg cells [10]. The activity in these studies have shown parallel effects as seen in the eye with AMD, or by primary RPE cell cultures.…”
Section: Introductionmentioning
confidence: 99%